2010
DOI: 10.1002/ccd.22569
|View full text |Cite
|
Sign up to set email alerts
|

Visible angiographic complications predict short and long‐term outcomes in patients with post‐procedural creatine‐phosphokinase elevation

Abstract: Post-PCI patients without visible angiographic complications have an excellent short and long term outcome. These findings call into question the need for routine CK-MB monitoring after PCI in the absence of clinical symptoms or angiographic complication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Finally, this study demonstrated an association between initial large thrombus before PCI, IPST during PCI, and impaired TIMI flow after PCI, which all represent different angiographic aspects of thrombotic burden, assessed at different times during the procedure, and which all may be targeted to improve the poor outcome observed in these patients. 19 , 20 Intriguingly, the vast majority of adverse events in patients with IPST occurred within the first few days after the procedure. Possibly, prolonged hospital observation following interventions complicated by IPST could be one strategy to minimize the poor outcome observed among these patients.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, this study demonstrated an association between initial large thrombus before PCI, IPST during PCI, and impaired TIMI flow after PCI, which all represent different angiographic aspects of thrombotic burden, assessed at different times during the procedure, and which all may be targeted to improve the poor outcome observed in these patients. 19 , 20 Intriguingly, the vast majority of adverse events in patients with IPST occurred within the first few days after the procedure. Possibly, prolonged hospital observation following interventions complicated by IPST could be one strategy to minimize the poor outcome observed among these patients.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies show that intraprocedural thrombotic events occur in approximately 3.5% of patients undergoing PCI for moderate or high-risk non-ST-segment elevation acute coronary syndrome, including 0.9% associated with new or enlarging thrombus, and such events are associated with higher rates of major adverse cardiac events and 30-day mortality (1). Visible angiographic complications during PCI portend significantly worse outcomes (6). All five HIT patients in our study had visible thrombosis resulting in cardiovascular collapse (▶ Figure 1).…”
mentioning
confidence: 68%
“…This might have contributed to the intrinsic link between IPST and residual thrombus and/or diminished coronary flow, and the possibility of fewer and/or lower pressure balloon/stent inflations to avoid worsening IPST. Most of the data currently existent relates intraprocedural complication to myocardial necrosis and not to recurrent thrombosis . Biondi‐Zoccai et al reviewed the incidence of IPST in 1,320 patients undergoing PCI with first generation DES in Italy.…”
Section: Discussionmentioning
confidence: 99%